Policy Capacity for Creative Economy Development in Central Java Province - Supradono, Bambang; Suwitri, Sri; Rina Herawati, Agustina (Iapa Proceedings Conference, 2024)
The performance of the creative economy in Central Java Province, based on data from the Ministry of Tourism and Creative Economy in 2021, managed to absorb a workforce of 1,410,155 people and create 3,146,702 business entities. The Creative Economy is vital in increasing community productivity and income, providing revenue for local governments, driving economic growth, and responding to various regional economic and social challenges. The Central Java Provincial Government has implemented regional regulations on creative economy development. These regulations involve a non-structural institution, the Creative Economy Committee, whose members consist of the creative economy community, academia, business, and media, to assist the Tourism Office, which has limited authority due to the decentralization of the division of concurrent affairs by the Local Government law. This qualitative research aims to analyze and measure the policy capacity of the two institutions in implementing creative economy development policies based on their duties and functions. Competencies were categorized into three general skills necessary for policy success - analytical, operational, and political - while policy capabilities were assessed at the individual, organizational, and system resource levels. The research findings show that the lack of policy capacity of the Tourism Office can be improved by collaborating with the Creative Economy Committee to improve policy capacity in developing effective and efficient creative economy policies in Central Java Province.